Antagonism of the Neurokinin-1 Receptor Improves Survival in a Mouse Model of Sepsis by Decreasing Inflammation and Increasing Early Cardiovascular Function. Issue 2 (February 2017) - Mella, Juan R.; Chiswick, Evan; Stepien, David; Moitra, Rituparna; Duffy, Elizabeth R.; Stucchi, Arthur; Remick, Daniel
Abstract : Objectives: Sepsis remains a serious clinical problem despite intensive research efforts and numerous attempts to improve outcome by modifying the inflammatory response. Substance P, the principal ligand for the neurokinin-1 receptor, is a potent proinflammatory mediator that exacerbates inflammatory responses and cardiovascular variables in sepsis. Design: The current study examined whether inhibition of the neurokinin-1 receptor with a specific antagonist (CJ-12, 255) would improve survival in the cecal ligation and puncture model of sepsis in adult female outbred mice. Setting: University basic science research laboratory. Measurements and Main Results: Neurokinin-1 receptor treatment at the initiation of sepsis improved survival in cecal ligation and puncture sepsis (neurokinin-1 receptor antagonist survival = 79% vs vehicle = 54%). Delaying therapy for as little as 8 hours postcecal ligation and puncture failed to provide a survival benefit. Neurokinin-1 receptor antagonist treatment did not prevent the sepsis-induced decrease in circulating WBCs, augment the early (6 hr postcecal ligation and puncture) recruitment of inflammatory cells to the peritoneum, or improve phagocytic cell killing of pathogens. However, the neurokinin-1 receptor antagonist significantly reduced both circulating and peritoneal cytokine concentrations. In addition, the cardiovascular variable, pulse distension (a surrogate for stroke volume) was improved in the neurokinin-1 receptor antagonist group during the first 6 hours of sepsis, and there was a significant reduction in loss of fluid into the intestine. Conclusion: These data show that early activation of the neurokinin-1 receptor by substance P decreases sepsis survival through multiple mechanisms including depressing stroke volume, increasing fluid loss into the intestine, and increasing inflammatory cytokine production.